Analisis Peran Dosen dalam Meningkatkan Motivasi Belajar Mahasiswa Pendidikan Teknik Mesin: Studi Literatur - Riyadi, Andrian; Muhtarom, Imam; Anggun Sari, Kartika (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – This study aims to explore the essential role of lecturers in enhancing student motivation in the Department of Mechanical Engineering Education at Faculty of Engineering Yogyakarta State University (FT UNY).Method – This study employs a qualitative approach with a focus on literature review to examine the role of lecturers in motivating students in the Department of Mechanical Engineering Education at FT UNY. Interviews are conducted as a complement to provide additional perspectives. The results are expected to offer in-depth insights for developing more effective teaching strategies.Findings – This study found that the role of lecturers as facilitators fostering independent learning, feedback providers, and creators of positive learning environments significantly contributes to students' learning motivation in the Department of Mechanical Engineering Education at UNY. Lecturers who provide targeted feedback help students improve their learning strategies, while strong interpersonal relationships increase their confidence and engagement. Additionally, relevant academic challenges and recognition of students' achievements drive learning motivation and prepare them for the professional world. These findings highlight the importance of lecturers' multidimensional roles in supporting students' academic growth. Research Implications – This study underscores the need for institutional support in enhancing lecturers’ roles to boost student motivation. Providing professional development, integrating technology, and adopting project-based learning can improve facilitation, feedback, and engagement, ultimately strengthening student autonomy and academic success.